Pharmacokinetic evaluation of prasugrel for the treatment of myocardial infarction. (April 2014) - Coons, James C; Schwier, Nicholas; Harris, Justin; Seybert, Amy L
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Prasugrel&logicalOpe1=OR&field2=articletitle&text2=Prasugrel&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Prasugrel is a novel P2Y12 inhibitor approved for treatment of patients with acute coronary syndrome (ACS) who undergo percutaneous coronary intervention (PCI). Areas covered: This article focuses on the pharmacokinetics of prasugrel and recently published pharmacodynamic and clinical studies. The authors searched PubMed and Ovid databases for English language pharmacokinetic, pharmacodynamic and clinical studies which described the use of prasugrel in human subjects and patients, published through October 2013. The keyword 'prasugrel' was used. Expert opinion: Prasugrel exhibits favorable pharmacokinetic and pharmacodynamic properties compared to clopidogrel. These effects have translated to significant clinical benefits, despite the increased bleeding risk, in the context of ACS with primary PCI. Recent clinical trial evidence does not support the use of prasugrel in other ACS settings at this time, including medical management of non-ST segment elevation myocardial infarction and routine pretreatment prior to angiography. Careful patient selection for prasugrel is also imperative, taking into account the need for maintenance dose reductions in certain patient subgroups. Antiplatelet decision making for high-risk patients in the future may be facilitated with the use of both genotypic and phenotypic characteristics, including platelet function, and should be an imperative for future research efforts.